Predicting prolonged length of stay after endoscopic transsphenoidal surgery for pituitary adenoma. Issue 6 (3rd May 2020) - Vimawala, Swar; Chitguppi, Chandala; Reilly, Erin; Fastenberg, Judd H.; Garzon‐Muvdi, Tomas; Farrell, Christopher; Rabinowitz, Mindy R.; Rosen, Marc R.; Evans, James; Nyquist, Gurston G.
Abstract : Background: Endoscopic transsphenoidal surgery (ETS) for the resection of pituitary adenoma has become more common throughout the past decade. Although most patients have a short postoperative hospitalization, others require a more prolonged stay. We aimed to identify predictors for prolonged hospitalization in the setting of ETS for pituitary adenomas. Methods: A retrospective chart review as performed on 658 patients undergoing ETS for pituitary adenoma at a single tertiary care academic center from 2005 to 2019. Length of stay (LoS) was defined as date of surgery to date of discharge. Patients with LoS in the top 10th percentile (prolonged LoS [PLS] >4 days, N = 72) were compared with the remainder (standard LoS [SLS], N = 586). Results: The average age was 54 years and 52.5% were male. The mean LoS was 2.1 days vs 7.5 days (SLS vs PLS). On univariate analysis, atrial fibrillation ( p = 0.002), hypertension ( p = 0.033), partial tumor resection ( p < 0.001), apoplexy ( p = 0.020), intraoperative cerebrospinal fluid (ioCSF) leak ( p = 0.001), nasoseptal flap ( p = 0.049), postoperative diabetes insipidus (DI) ( p = 0.010), and readmission within 30 days ( p = 0.025) were significantly associated with PLS. Preoperative continuous positive airway pressure (CPAP) (odds ratio, 15.144; 95% confidence interval, 2.596‐88.346; p = 0.003) and presence of an ioCSF leak (OR, 10.362; 95% CI, 2.143‐50.104; p = 0.004) remained significant on multivariable analysis. Conclusion: For patients undergoing ETS for pituitary adenomas, an ioCSF leak or preoperative use of CPAP predicted PLS. Additional common reasons for PLS included postoperative CSF leak (10 of 72), management of DI or hypopituitarism (15 of 72), or reoperation due to surgical or medical complications (14 of 72).